Evaluation of Climates for Residential Real Estate Developers in the Czech Republic and Austria - Bachratá, Klára; Černá, Iveta, 1979-; Křenková, Eva; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis deals with climates for residential real estate developers in the Czech Republic and Austria. Its aim is to provide recommendations for the Czech residential real estate developers and authorities overlooking the process by studying, assessing, and comparing the Czech residential real estate climate for developers with the one in Austria. The following research questions are connected to the thesis’s aim: What are the favorable and hindering aspects of residential real estate development in the Czech Republic and Austria? Which areas of Czech residential real estate development are more and less developed? How can the Czech residential real estate development sector be enhanced, based on the example of Austria? The questions are answered using the PESTLE, Porter's Five Forces and the SWOT analyses, and a scoring model composed of four indicators: mortgage rate, permits, buildings started and buildings completed.
Vedoucí práce: Iveta Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses